PELATIHAN PENGEMBANGAN DESA WISATA DI KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - Ohello, Marselitha Trivena (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Jailolo Subdistrict, West Halmahera Regency, has natural resource potential with the charm of an excellent coastal area if it is developed into a Tourism Village. Because of the limited knowledge of the community on the development of village tourism objects, it is necessary to conduct Tourism Village Development training. This training is carried out using a participatory approach, where participants take an active role. This participatory method includes lectures, discussions, questions and answers, brainstorming, and practice. The participants in this training were 30 people from 5 villages in the Jailolo District. The results of providing this tourist village training material can increase the participants' understanding of managing a tourist village well so that they can apply all the material that has been delivered in their respective regions